The Labor Absorbtion in Food and Beverages of Small Business Enterprises in Aceh Province - Ishak Hasan, Ishak Hasan; Yasrizal, Yasrizal (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
The competition of labor market in Asean Economic Society will be determined bythe labor’s productivity. Small businesses of foods and beverages is the highest subsector which recruit the labor in Aceh. In 2010 there were 929.910 small businesseswhich were able to recruit 2.152.981 labor or around 31,99%. There are threevariables impact the absorbtion of labor, the wages, labor productivity and capital.This research uses multiple regression technique to analyse data. The techniqueanalysis used to find the impact of wages, productivity and capital to the absorbtionof labor in small businesses and enterprises. Based on research finding, thecompetitive advantage of Indonesian labor is at the sixth rank of ten countries inASEAN. The research also found that productivity has significant impact to theabsorbtion of labor while capital and wages have no significant impact to theabsorbtion of labor in Aceh Province